A comparison of CH4, N2O and CO2 emissions from three different cover types in a municipal solid waste landfill. (3rd April 2017) - Wang, Xiaojun; Jia, Mingsheng; Lin, Xiangyu; Xu, Ying; Ye, Xin; Kao, Chih Ming; Chen, Shaohua
ABSTRACT: High-density polyethylene (HDPE) membranes are commonly used as a cover component in sanitary landfills, although only limited evaluations of its effect on greenhouse gas (GHG) emissions have been completed. In this study, field GHG emission were investigated at the Dongbu landfill, using three different cover systems: HDPE covering; no covering, on the working face; and a novel material-Oreezyme Waste Cover (OWC) material as a trial material. Results showed that the HDPE membrane achieved a high CH4 retention, 99.8% (CH4 mean flux of 12 mg C m -2 h -1 ) compared with the air-permeable OWC surface (CH4 mean flux of 5933 mg C m -2 h -1 ) of the same landfill age. Fresh waste at the working face emitted a large fraction of N2 O, with average fluxes of 10 mg N m -2 h -2, while N2 O emissions were small at both the HDPE and the OWC sections. At the OWC section, CH4 emissions were elevated under high air temperatures but decreased as landfill age increased. N2 O emissions from the working face had a significant negative correlation with air temperature, with peak values in winter. A massive presence of CO2 was observed at both the working face and the OWC sections. Most importantly, the annual GHG emissions were 4.9 Gg yr -1 in CO2 equivalents for the landfill site, of which the OWC-covered section contributed the most CH4 (41.9%), while the working face contributed the most N2 O (97.2%). HDPE membrane is therefore, a recommended cover material for GHG control. Implications : Monitoring of GHG emissions at three different cover types in a municipal solid waste landfill during a 1-year period showed that the working face was a hotspot of N2 O, which should draw attention. High CH4 fluxes occurred on the permeable surface covering a 1- to 2-year-old landfill. In contrast, the high-density polyethylene (HDPE) membrane achieved high CH4 retention, and therefore is a recommended cover material for GHG control.